Professional Network Community for Training Youth Workers: Conceptual Framework and Prerequisites for the Creation - E. M. Kharlanova; E. V. Shirokova; O. V. Besschetnova; A. B. Fedulova (Высшее образование в России)
Currently, in the context of the transition to hybrid education, new network forms of communication and interaction of teachers, students as well as specialists are in demand in the framework of personnel training, research and professional activities. The article reveals the main aspects of the integrated network community for training professionals working with youth in the field of educational and youth social policy. Network community can be viewed as an important resource for the development of both the participants themselves and the specific professional sphere. The purpose of the article is to describe the conceptual framework of a professional network community for training personnel for working with youth in the context of social, educational and youth policy and identify the prerequisites for its creation.In the course of the work, we used such methods as structural and functional analysis, system synthesis, modeling and an online survey. The sample comprised university students, faculty members, and youth workers (n = 147) from six federal districts of Russia.The conceptual framework of the professional network community presented on the basis of systemic-synergetic and constructive methodological approaches enables 1) to formulate its idea as a collaboration for personnel training, scientific research, joint projects implementation and self-development of participants; 2) to identify systemic contradictions, the solution of which is directed by the interaction of community members; 3) to determine the axiological basis, purpose, objectives and stages of deployment; 4) to identify the degree of its relevance, the presence of common interests among all its participants on the basis of the results of empirical research that may be useful in the professional network communities design.